Presence of Protease Inhibitor 9 and Granzyme B in Healthy and Pathological Human Corneas - Reinstein Merjava, Stanislava; Kossl, Jan; Neuwirth, Ales; Skalicka, Pavlina; Hlinomazova, Zuzana; Holan, Vladimir; Jirsova, Katerina (Biology, 2022)
The aim of this study was to find out whether protease inhibitor 9 (PI-9) and granzyme B (GrB) molecules that contribute to immune response and the immunological privilege of various tissues are expressed in healthy and pathological human corneas. Using cryosections, cell imprints of control corneoscleral discs, we showed that PI-9 was expressed particularly in the endothelium, the superficial and suprabasal epithelium of healthy corneas, limbus, and conjunctiva. GrB was localized in healthy corneal and conjunctival epithelium, while the endothelium showed weak immunostaining. The expression of PI-6 and GrB was confirmed by qRT-PCR. Increased expression levels of the PI-9 and GrB genes were determined when the corneas were cultured with proinflammatory cytokines. Fluorescent and enzymatic immunohistochemistry of pathological corneal explants (corneal melting and herpes virus keratitis) showed pronounced PI-9, GrB, human leucocyte antigen (HLA)-DR, and leukocyte-common antigen (CD45) signals localized in multicellular stromal infiltrates and inflammatory cells scattered in the corneal stroma. We conclude that increased expression of the PI-9 and GrB proteins under pathological conditions and their upregulation in an inflammatory environment indicate their participation in immune response of the cornea during the inflammatory process.
Keywords: granzyme B; corneal endothelium; protease inhibitor 9; corneal epithelium; cornea